Pemanfaatan Dana Zis (Zakat, Infaq, Sedekah) Pada Program Peduli Pendidikan Di DT Peduli Sumut - Dwi Nur Annisa; Marliyah Marliyah (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
Utilization of ZIS (Zakat, Infaq, Alms) Funds in the Education Care Program at Dt Peduli North Sumatra. The aim of this research is to find out: how ZIS funds are used for one of the flagship Education Care programs at DT Peduli North Sumatra. What are the inhibiting factors in this utilization, as well as how to overcome obstacles related to the use of ZIS funds in education care programs. This research is a qualitative descriptive research with an inductive approach. Data was collected using triangulation techniques, namely observation, interviews and documentation. Data analysis was carried out by presenting data, reducing data and drawing conclusions. The research results showed that there were two educational financing programs carried out by this institution, namely the AIS Scholarship program and the Excellence Student Scholarship. These two programs are financed from the utilization of ZIS funds that have been collected. The use of ZIS funds for one of the flagship Education Care programs at DT Peduli North Sumatra has gone well and provided positive benefits